Nijmegen-Holdeurn ware from the western canabae legionis at Nijmegen (NL): some remarks on chronological and spatial analysis - Kloosterman, René (Rei Cretariae Romanae Fautorum Acta, 2017)
Wheel turned Roman pottery was first introduced to the Lower Rhineland by the legions participating in the German campaigns commenced by Augustus in the second decade BC. These first imports, especially the fine tableware, still betrayed strong Mediterranean influences, as did some of the pottery produced by the legions themselves at their bases. In the course of the 1st century AD, demand created by early incarnations of urban settlements like Cologne, Xanten and Nijmegen and the establishment of a more or less permanent military presence along the Rhine led to the birth and expansion of a provincial pottery industry. These regional potteries, based in urban centres and in the countryside, developed a Gallo-Roman style of their own which gradually moved away from its Mediterranean origins. From the Claudian period onwards, a substantial part of the pottery in use in the Lower Rhineland came from these regional potteries, of which Cologne became one of the principal centres.